Digital Competency Components Most Relevant To Police Intelligence For Cybercrime Prevention Systematic Literature Review - Salfiani Sari (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to map the most relevant digital competency components for police intelligence, identify intelligence technologies used for cybercrime prevention, and explain how these technologies affect the effectiveness of prevention through early detection, prediction, and response, considering the role of cybercrime dynamics as factors that can moderate or suppress the effectiveness of strategies. The method used was a systematic literature review with searches on Google Scholar and ScienceDirect using a combination of English and Indonesian keywords, as well as Boolean AND and OR operators. The study selection process is carried out through the stages of identification, screening of titles and abstracts, full text review, and determination of the final study based on inclusion criteria that emphasize relevance to law enforcement and police intelligence, discussion of digital competence or intelligence technology, novelty of publications, and quality of scientific sources. The selected studies were then summarized, extracted into a synthesis table, and analyzed using narrative synthesis and thematic analysis. The results of the study show that the dominant digital competencies include information literacy, technological proficiency, digital communication, critical and analytical thinking skills, ethical and legal awareness, and continuous adaptive learning. The most commonly identified intelligence technologies include artificial intelligence and machine learning, cybersecurity software, cloud computing, mobile forensics, integrated cyber investigation platforms, as well as blockchain exploration for data integrity and digital evidence. These technologies tend to improve the effectiveness of prevention by accelerating